Geophysics Quantitative Research Mapping of Geomagnetic Method Implementation for Geothermal Exploration: A Bibliometric Analysis - Magribi, Fatin; Asrizal, Asrizal; Amir, Harman; Fitri, Leni (Department of Physics, Universitas Negeri Padang, 2025)
Indonesia is the second country with the largest geothermal potential in the world because Indonesia has many volcanoes and active tectonic activity causes the formation of geothermal energy around the mountain. The population growth rate in Indonesia is soaring, this condition is inversely proportional to the availability of non-renewable energy in Indonesia. The solution is to look for alternative energy substitutes, namely renewable energy, for example geothermal. This study aims to see the development and trends in the use of geomagnetic methods for geothermal exploration. The method used is bibliometric with a quantitative approach. Data retrieval and processing used the publish or perish application integrated with Google Scholar. The data used were 200 articles published on Google Scholar during 2015-2025 and 80 keywords found. Data analysis techniques by looking at the development of article trends each year, data network visualization, data overlay visualization and data density visualization. The results obtained from publications with the topic of geomagnetic method utilization trends for geothermal exploration in 2015-2025 increased every year. For the results of data network visualization, not only Indonesia but various international countries have also begun to utilize geothermal. The results of the visualization of Indonesia's geothermal data overlay were much sought after in 2019.